Hubungan Tingkat Pengetahuan Dan Sikap Perawat Tentang Pemberian Obat Terhadap Tindakan Pendokumentasian Keperawatan - Endang Epi Sri Sumarni; Gamya Tri Utami; Veny - Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research aims to determine the relationship of the level of knowledge and attitude of nurses on drug giving  in nursing documentation . The design of this research  was" descriptive correlative " with “cross-sectional " approach . This research was conducted in medical surgical room Eka Hospital Pekanbaru . Total sample was 58 people’s which taken using purposive sampling technique with attention to inclusion criteria. Measuring instruments used in this research is a questionnaire and observation sheet to measure knowledge , attitudes and actions. The analysis used is univariate and bivariate chi square test . The results showed the correlation between knowledge and attitudes about drug giving in nursing documentation ( p - value < 0.05 ). Nurses are expected to do drug giving in nursing documentation b medication according to Potter Perry’s standard (2010) is name of patien, name of drug, dose, time, and documentation, so there is no mistake in the act of drug giving. Keywords : Knowledge , attitudes , actions , documentation